The Role of Complex Perinatal Anamnesis in the Formation of Bronchial Asthma in Children (Literature Review) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Bronchial asthma is widespread and tends to steadily increase in incidence in children, shifting the onset to an earlier age. It was revealed that the majority of children with bronchial asthma have a history of perinatal damage to the central nervous system. However, it should be noted that the mechanisms of influence of perinatal damage to the central nervous system on the formation of bronchial asthma are numerous and have not yet been sufficiently studied. All this proves the need for preventive measures for the physiological course of pregnancy in women. Since chronic hypoxia, acute asphyxia during childbirth and, especially, the resulting premature birth contribute to the development of not only neurological pathology, but also multiple organ disorders. Moreover, in children who have suffered perinatal damage to the nervous system, somatic pathology, including bronchial asthma, is much more severe.